0
$\begingroup$

Let $V$ be a vector space and let $A, B$ be subspaces of V. The sum of $A, B$ is the subspace of $V$ given by $$ A + B = \{a+b : a\in A, b\in B\} $$ Moreover if $A \cap B=\{0\}$ then the sum of $A,B$ is called the inner direct sum of $A,B$ and is denoted with $A \oplus B$. Let $A, B, C$ be subspaces of $V$ with $C = A + B$. Then $$ C = A \oplus B \iff \forall c \in C, \exists! a\in A, \exists! b \in B : c = a + b $$

If we replace on the right hand side $\forall c\in C$ with $\exists c\in C$ then does the equivalence still hold?

$\endgroup$
6
  • $\begingroup$ Your question does not seem to be clear. $\endgroup$
    – nature1729
    Jul 15 '18 at 14:51
  • $\begingroup$ Take $A \cap B = \{0\}$ and $C = A$, then for any $c \in C$ (in particular: $\exists c \in C$ s.t. ...) there are unique $a \in A$ and $b \in B$ s.t. $c = a + b$, namely $a = c$ and $b = 0$, but $C \neq A + B$, hence $C = A \oplus B$ is not true. $\endgroup$
    – qwertz
    Jul 15 '18 at 14:54
  • $\begingroup$ @qwertz i restated my quastion because it was not clear enough. Thank u very much for your answer $\endgroup$ Jul 15 '18 at 15:14
  • $\begingroup$ @nature1729 u are right. I restated my question. $\endgroup$ Jul 15 '18 at 15:14
  • 1
    $\begingroup$ @AnyAD unique. So $\exists !$ means there is EXACTLY ONE $\endgroup$ Jul 15 '18 at 15:38
1
$\begingroup$

The equivalence still holds: We have that \begin{align*} C = A \oplus B &\iff \forall c \in C, \exists! a\in A, \exists! b \in B : c = a + b \\ &\,\implies \exists c \in C, \exists! a\in A, \exists! b \in B : c = a + b \end{align*} because we can choose $c = 0$. To show the other implication $$ \exists c \in C, \exists! a\in A, \exists! b \in B : c = a + b \implies \forall c \in C, \exists! a\in A, \exists! b \in B : c = a + b $$ let $c \in C$ such that for $c = a + b$ with $a \in A$, $b \in B$ the summands $a, b$ are unique.

Let $x \in A \cap B$. It then follows from $x \in A$ that $a + x \in A$ and it follows from $x \in B$ that $b - x \in B$. We have that $$ c = a + b = (a + x) + (b - x) $$ so it follows from the uniqueness of $a, b$ that $a+x = a$ and $b-x = b$. Both equations show that $x = 0$. This shows that $A \cap B = \{0\}$ and together with $C = A+B$ that $C = A \oplus B$.

For subspaces $A, B, C \subseteq V$ with $C = A + B$ one can show more generally that the following conditions are all equivalent:

  • $C = A \oplus B$, i.e. $A \cap B = 0$
  • $\forall c \in C: \exists! a \in A \exists! b \in B: c = a + b$
  • $\forall c \in C: \exists! a \in A \exists b \in B: c = a + b$
  • $\forall c \in C: \exists a \in A \exists! b \in B: c = a + b$
  • $\exists! a \in A \exists! b \in B: 0 = a + b$
  • $\exists! a \in A \exists b \in B: 0 = a + b$
  • $\exists a \in A \exists! b \in B: 0 = a + b$
$\endgroup$
1
  • $\begingroup$ You are excellent $\endgroup$ Jul 15 '18 at 15:47

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.